Partitioning of arsenic in slurry feed entrained-flow gasifier with wet gas cooling cleaning system. (1st December 2019) - Du, Yuying; Li, Li; Huang, Qifei; Yan, Dahai; Li, Xuebing; Qi, Yangjian; Wang, Mingxia; Zhu, Xuemei; Hao, Yaqiong; Liu, Meijia
Abstract: Slurry feed entrained-flow gasifier has been applied more and more in waste treatment. However, the data on the distribution and emission of arsenic (As) in such gasifiers are very limited. The fate of As in gasification system is closely related to the conditions of gasifier and subsequent gas treatment processes. In this paper, the partitioning of As in slurry feed entrained-flow gasifier with wet gas cooling cleaning system is determined. The influence of feedstock and process water are studied. It is shown that co-gasification waste with coal and the redox condition of process water have little effect on the overall distribution of As. 91.7–94.5% of As is distributed to flash wastewater under water-oxidizing condition and 85.5–99.7% of As partitions into the wastewater under water-reducing condition. Less than 4% of As enters the raw syngas. Under the condition of waste addition and reducing water, As has the risk of being released into the atmosphere with the exhaust gas (8.4–57.0 μg/Nm 3 ). According to the data detected under water-oxidizing condition, the concentration of As in clarified water is 0.367–1.195 ppm, and that in clarifier solid is 34.06–159.84 ppm. Therefore, the reuse of clarified water as process water of wet gas treatment system and clarifier solid as feedstock of gasifier may lead to As recycling in the gasification system. Highlights: Waste co-gasification and water redox condition have little effect on As partition. In ox- and red- water, 91.7–94.5% and 85.5–99.7% As enter wastewater respectively. Less than 4% of As partitions into the raw syngas. With waste co-gasification and reducing water, As has release risk with exhaust gas. The reuse of clarified water and clarifier solid may lead to As recycling in system.